Multiband OFDM for Cognitive Radio – A Way for Cyclostationary Detection and Interference Cancellation - Avila J; Thenmozhi K (Institute of Advanced Engineering and Science, 2016)
With the tremendous growth in wireless technology there has been a shortage in the spectrum utilized for certain applications while some spectrum remains idle. To overcome this problem and for the efficient utilization of the spectrum cognitive radio is the suitable solution.Multiband OFDM can be easily modeled as cognitive radio, a technology that is employed for utilizing the available spectrum in the most efficient way. Since sensing of the free spectrum for detecting the arrival of the primary users is the foremost job of cognitive, here cyclostationary based spectrum sensing is carried out. Its performance is investigated using universal software defined radio peripheral (USRP) kit which is the hardware test bed for the cognitive radio system. Results are shown using Labview software. Further to mitigate the interference between the primary and cognitive users a modified intrusion elimination (AIC) algorithm had been proposed which in turn ensures the coexistence of both the users in the same wireless environment.